Трагическое в философии монтажа. К интерпретации раздвоенности образа главной героини романа Л.Н. Толстого „Анна Каренина” - Królikiewicz, Natalia (Studia Rossica Posnaniensia, 2014)
The article is an attempt at interpreting the tragic split in the artistic image of Anna Karenina – the main character in Leo Tolstoy’s novel – from the perspective of the montage theory. The author seeks to demonstrate that the concept of montage (which was formulated by S. Eisenstein), when used as a research technique, plays a fundamental role in analyzing this literary text. A literary analysis of montage revealed the presence of a montage of antitheses, analogies, repetitions as well as leitmotifs, and emphasized the role of cinematographic detail and the main protagonist’s split consciousness. It allowed the author to uncover important contexts for interpreting the category of tragedy.